Women's health, hormonal balance, and personal autonomy - Segarra, Ignacio; Menárguez, Micaela; Roqué, María Victoria (Frontiers in Medicine, 2023)
Hormonal-based contraception disrupts hormonal balance, creating artificial states of anovulation, threatening women’s health. We review their main adverse effects and mechanisms on: accelerated ovarian aging, mental health (emotional disruptions, depression, suicide), sexuality (reduced libido), cardiovascular (brain stroke, myocardial infarction, hypertension, thrombosis) and oncological (breast, cervical, endometrial cancers). Other “collateral damage” includes tainted adverse effects communication, scientific mistrust, poor physician-patient relationship, patient burden, economic drain to the healthcare system, and environmental pollution. Hormone-sensitive tumors created dilemmas owing potential dual effects: preventing some cancers versus higher risk for others, remains controversial with denial or dismissal as non-relevant adverse effects, information avoidance and scientific criteria modification. This deficient clinical assessment challenges women’s health and right to autonomy. Reversing it demands anthropological integration of sexuality: the genital bodily union fails to integrate the intimate relational expression of their persons with complete sexual satisfaction, intertwining feelings of trust, safety, tenderness and endorsement of women’s femininity.